Characterization of secondary phosphine oxide ligands on the surface of iridium nanoparticles. Issue 32 (2nd August 2017) - Cano, Israel; Martínez-Prieto, Luis M.; Fazzini, Pier F.; Coppel, Yannick; Chaudret, Bruno; van Leeuwen, Piet W. N. M.
Abstract : The coordination mode of secondary phosphine oxide ligands on the surface of iridium nanoparticle catalysts was elucidated by solid-state NMR. Abstract : The synthesis of iridium nanoparticles (IrNPs) ligated by various secondary phosphine oxides (SPOs) is described. This highly reproducible and simple method via H2 reduction produces well dispersed, small nanoparticles (NPs), which were characterized by the state-of-the-art techniques, such as TEM, HRTEM, WAXS and ATR FT-IR spectroscopy. In particular, multinuclear solid state MAS-NMR spectroscopy with and without cross polarization (CP) enabled us to investigate the different binding modes adopted by the ligand at the nanoparticle surface, suggesting the presence of three possible types of coordination: as a purely anionic ligand Ir–P(O)R2, as a neutral acid R2 P–O–H and as a monoanionic bidentate H-bonded dimer R2 P–O–H⋯OPR2 . Specifically, the higher basicity of the dicyclohexyl system leads to the formation of IrNPs in which the bidentate binding mode is most abundant. Such cyclohexyl groups are bent towards the edges, as is suggested by the study of 13 CO coordination on the NP surface. This study also showed that the number of surface sites on faces available for bridging CO molecules is higher than the number of sites for terminal CO species on edges and apices, which is unexpected taking into account the small size of the nanoparticles. In addition, the IrNPs present a high chemoselectivity in the hydrogenation of cinnamaldehyde to the unsaturated alcohol.